Development of Educational Game-Based E-Modules to Improve Autonomous Learning Skills - Yana, Indah; Surur, Miftahus; Rakhman, Fathor; Sri Darmawati, Lusi Endang (STKIP PGRI SITUBONDO, 2024)
The purpose of this project is to create learning materials in the form of e-modules based on instructional games, as well as to assess the viability of the materials through expert testing and evaluate their efficacy in enhancing self-directed learning skills. The creation of this medium is predicated on the findings of an examination of the traits of pupils who depend more on teacher explanations and are less engaged in their learning. The five steps of the ADDIE model—analysis, design, development, implementation, and evaluation—make up the employed development process. Based on the media and material experts' validity test findings, the results of developing educational game-based e-module goods in economic disciplines revealed a 95% and 91% feasibility percentage in the very good and practicable to be used in learning categories, respectively. According to the findings of the examination of the responses from students who gave a favorable answer of ≥80%, which came to 88%, there were several excellent categories. Based on the analysis's findings, it can be said that the e-module does a good job of enhancing students' ability to study independently.